Impact of Perceived Vulnerability and Benefits on Adolescent Smoking Cessation Motivation - Setyoadi; Aisyana, Lala; Sari, Efris Kartika; Ismail, Dina Dewi Sartika Lestari (Al-Hijrah Indonesia, 2025)
Background: Most smoking among adolescents aged 15-19 years is associated with a psychosocial crisis, as they are still searching for their identity. Factors such as perceived vulnerability and perceived benefits can lead adolescents to start smoking. Purpose: The purpose of this study was to determine the relationship between perceived vulnerability and perceived benefits and motivation for smoking cessation among adolescents. Methods: The research design uses an analytical observational design with a cross-sectional approach. The research sample consisted of adolescent smokers selected using a cluster random sampling technique, resulting in 136 participants. Data for variables were collected using the Perceived Vulnerability to Disease (PVD), Perceived Risks and Benefits Questionnaire (PRBQ), and Smoking Cessation Motivation Questionnaire (Q-MAT), which were modified by the researchers and tested for validity and reliability. The research data were analyzed using the Spearman Rank Test. Results: The results showed that 97.8% of participants had a positive perceived vulnerability, 97.1% had a positive perceived benefit, and 71.3% had a high motivation for smoking cessation. There was a significant relationship between perceived vulnerability and perceived benefits with motivation for smoking cessation, with a significant p-value of 0.000 and correlation values of +0.478 and +0.643. Conclusions: Adolescents' motivation to quit smoking is shaped by their awareness of health risks and the benefits of quitting, such as improved well-being and financial savings. Nursing-based interventions, including counseling, support groups, and school health campaigns, play a crucial role in reinforcing this motivation and ensuring long-term cessation.